Problema inverso aplicado em imagens de biosusceptometria AC de nanopartículas magnéticas - Alvarez, Marcelo Dante Tacconi [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Magnetic nanoparticles (MNPs) have been widely proposed for various purposes in the medical field. Due to their high versatility, whether their reduced size of nanometers or their composition and coating, magnetic nanoparticles have theranostic potential (diagnosis and treatment using the same MNP). To detect these MNPs in biological environments, techniques such as magnetic resonance (MRI), magnetic particle imaging (MPI), and superconducting quantum interference devices (SQUIDs) are used. However, such types of equipment have disadvantages and restrictions regarding their use. Therefore, the AC Biosusceptometry (ACB) technique appears with great potential for the MNPs detection in real-time and in vivo, allowing for several studies in this area. ACB has high versatility because it is portable, easy to handle, presents very low cost, and does not require the use of a controlled environment. Thus, the purpose of this work is to characterize the BAC system with different MNPs available on the market, and synthesized by our group, through experiments and computer simulations, construction of phantoms, and mathematical techniques. Thus, obtaining this information about the system, it was possible to increase its applicability, solving the inverse problem related to this system, which allowed quantifying the MNPs. In the present work, for the first time, this quantification was performed using images obtained from specific phantoms, but in the future, they may be performed in vivo. As a result, BAC may be elevated to the level of other techniques considered to be of a high standard and with great potential, such as magnetorelaxometry and the MPI system, to be used in the market and in clinical medicine.

As nanopartículas magnéticas (NPMs) têm sido amplamente propostas para diversos fins na área médica. Devido à sua alta versatilidade, seja no tamanho reduzido a nanômetros ou na sua composição e revestimento, as nanopartículas magnéticas possuem potencial teranóstico (diagnóstico e tratamento utilizando uma mesma NPM). A fim de se detectar essas NPMs em ambientes biológicos, são utilizadas técnicas como a ressonância magnética (MRI), imageamento de partícula magnética (MPI) e dispositivos supercondutores de interferência quântica (SQUIDs). No entanto, tais equipamentos possuem desvantagens e restrições quanto ao seu uso. Sendo assim, a técnica de Biosusceptometria AC (BAC) surge com grande potencial para detecção de NPMs em tempo real in vivo, permitindo diversos estudos nessa área. A BAC possui alta versatilidade por ser portátil, de fácil manejo, baixíssimo custo e dispensar o uso de ambiente controlado. Dessa forma, a proposta desse trabalho foi caracterizar o sistema BAC em relação a diferentes NPMs disponíveis no mercado, e sintetizadas por nosso grupo, através de experimentos e simulações computacionais, construção de fantomas e técnicas matemáticas. Assim, obtendo essas informações sobre o sistema, foi possível aumentar sua aplicabilidade, resolvendo o problema inverso referente a esse sistema, o que permitiu além de detectar, quantificar as NPMs. Neste presente trabalho, pela primeira vez, essa quantificação foi realizada em imagens obtidas utilizando fantomas específicos, porém futuramente poderão ser realizadas in vivo. Com isso, a BAC poderá ser elevada a nível de outras técnicas consideradas de alto padrão e com grande potencial de serem empregadas no mercado e na clínica médica como a magnetorelaxometria e o sistema MPI.
Inverse problem aply in AC biosusceptometry images of magnetic nanoparticles
Keywords: Magnetic nanoparticles; Medical instrumentation; Nanomedicine; AC biosusceptometry; Biomagnetism; Magnetic inverse problem; Nanomedicina; Biosusceptometria AC; Biomagentismo; Nanopartículas magnéticas; Problema inverso magnético; Instrumentação médica